2019
DOI: 10.1002/cyto.b.21845
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric features of incidental indolent T lymphoblastic proliferations

Abstract: Indolent T lymphoblastic proliferations have been reported rarely in extramedullary and extrathymic tissues. Recent work has identified these indolent T lymphoblast populations to be mostly CD4+/CD8+ (characterized by immunohistochemistry), with only limited immunophenotypic evaluation of these populations by flow cytometry (FC). We retrospectively reviewed our institutional FC archives and identified 12 samples from 10 patients with incidental T lymphoblastic populations. Samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Interestingly, Fromm et al . recently identified populations of T cells with varying stages of maturation in patients with iT‐LBP, suggesting that continuous release of immature T cells occurs from the thymus or extrathymic locations of T‐cell maturation 14 . Certainly, the absence of LMO2 expression in iT‐LBP is consistent with a thymic anatomical origin for iT‐LBPs, as TdT+ T cells in the thymus lack LMO2 expression 2,11 .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, Fromm et al . recently identified populations of T cells with varying stages of maturation in patients with iT‐LBP, suggesting that continuous release of immature T cells occurs from the thymus or extrathymic locations of T‐cell maturation 14 . Certainly, the absence of LMO2 expression in iT‐LBP is consistent with a thymic anatomical origin for iT‐LBPs, as TdT+ T cells in the thymus lack LMO2 expression 2,11 .…”
Section: Discussionmentioning
confidence: 87%
“…These findings are different from most IHC stain results reported, which were usually CD4+CD8+. TdT and cCD3 were almost always positive by either FCM anylysis or IHC stains, but the expression of sCD3, CD2, CD5, CD7, CD10, CD1a, and CD34 was variable [2,14]. CD33, a myeloid marker, is reportedly expressed in some iT-LBP cases [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…BM studies showed the following karyotype (Fig. 3a): 47,XY,add(12)(p12),+21 [5]/ 49,sl,+8,+9 [1]/46,XY [14]/92,XXYY [5]. Fluorescence in situ hybridization (FISH) analysis showed loss of ETV6 (12p13) and gain of 21q22 (RUNX1) in 11.5%, and gain of 9q34 (ASS1, ABL1) in 4.5% of nuclei (Fig.…”
Section: Casementioning
confidence: 99%
“…Normal phenotypes may also be affected by microenvironmental factors, unrelated to treatment; Gadgeel and colleagues suggest in this issue (Gadgeel et al, 2021) that phenotypic maturation patterns in ectopic intrathyroidal thymic tissue differ from those described in normal thymus and thymoma (DiGiuseppe & Wood, 2019). Along these lines, microenvironmental cues have also been suggested to explain the apparent association between extrathymic immature T‐cell populations and Castleman disease (Fromm et al, 2020). One must also be alert for unexpected phenotypes in hematolymphoid neoplasms, such as the case of CD45‐negative follicular lymphoma reported by Khanlari and colleagues in the current issue (Khanlari et al, 2021).…”
mentioning
confidence: 99%